Training System and Administrative Formation – What is Training in Administrative Jurisprudence, Legal Framework for Training and Configuration: a Comparative Study (The International Journal for Scientific Research, 2023)
Building an effective training and training strategy that is compatible with the needs and objectives of government organizations in Jordan and Morocco is one of the important functions of human resource management, which crystallizes through studying the strengths and weaknesses of employees, identifying workplaces that are lacking and need repayment or development, and determining the goal of training and training. Training must be viewed as an investment process that requires calculating the profit and return from it, and not just a routine work represented in implementing training programs here or there according to formal procedures that do not adopt the appropriate scientific method.
Keywords: Training; Configuration; Legal Framework; Organization Analysis; Duties of the Employee; Highly Effective; Governmental Organizations; Management Jurisprudence